Effect of rhodium-copper bimetallic nanozymes on apoptosis of osteosarcoma cells - WANG Hanjie; YE Yuting; GUANG Yiran; HUANG Zhangrui; ZHONG Jingping (Guangxi Yike Daxue xuebao)
Objective To construct a graphdiyne-supported rhodium-copper bimetallic (Rh-Cu/GDY) nanozyme system through an innovative preparation process, so as to explore the unique enzyme-like activity of the nanozymes and their effect on the apoptosis of osteosarcoma (OS) cells. Methods Synthesis and characterization of Rh-Cu/GDY nanozymes were carried out by the hydrothermal method. The peroxidase-like (POD) activity, catalase-like (CAT) activity of Rh-Cu/GDY, and its ability to consume glutathione (GSH) were accurately detected in vitro. Additionally, the abilities of Rh-Cu/GDY to catalyze hydrogen peroxide (H2O2) to generate oxygen (O2) and hydroxyl radicals (•OH) and to consume GSH through its CAT and POD enzyme activities were detected using a dissolved oxygen meter, 3, 3', 5, 5'-tetramethylbenzidine (TMB), and 5, 5'-dithiobis (2-nitrobenzoic acid) (DTNB) fluorescent probes. The cytotoxicity and anti-tumor activity of Rh-Cu/GDY against human umbilical vein endothelial cells (HUVECs), OS cells 143B and MG63 were detected by cell counting kit-8 (CCK-8). The levels of intracellular reactive oxygen species (ROS) in each group of cells were detected using HPF and [Ru (DPP)3]Cl2 fluorescent probes. The JC-1 mitochondrial fluorescence staining technique was used to evaluate the mitochondrial level of tumor cells. The Ki67 immunofluorescence staining experiment was conducted to detect the expression of Ki67 protein in tumor cells. The western blotting experiment for Bax protein was performed to evaluate the expression of intracellular Bax protein in tumor cells treated with nanozymes at different concentrations. Results Transmission electron microscopy (TEM), Zeta potential analysis, high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and energy-dispersive X-ray spectroscopy mapping (EDS-mapping) confirmed the successful synthesis of the Rh-Cu/GDY nanozymes. The enzymelike activity assay showed that Rh-Cu/GDY nanozymes could effectively mimic POD and CAT activities while consuming GSH. CCK-8 experimental results confirmed that Rh-Cu/GDY nanozymes had good biocompatibility and anti-tumor ability. Compared with the blank control group, the level of intracellular ROS in the 143B cells of the Rh-Cu/GDY group showed an extremely significant upward trend. Compared with the blank control group, the expression of red fluorescence of JC-1 mitochondria in the Rh-Cu/GDY group was significantly increased. Only weak fluorescence of Ki67 was observed in the Ki67 immunofluorescence assay, and the expression level of Bax protein was also gradually increased with the increase of the concentration of the nanozymes. Conclusion The Rh-Cu/GDY nanozymes with multiple enzyme-like activities are successfully prepared, and they can achieve the effect of killing OS by promoting the generation of ROS in OS cells and inducing apoptosis. The Rh-Cu/GDY nanozymes are is an anti-tumor nanomaterial with promising prospects.